In vivo investigation of (2-hydroxypropyl)-β-cyclodextrin-based formulation of spironolactone in aqueous solution for paediatric use - Lopalco, Antonio; Manni, Annachiara; Keeley, Alexander; Haider, Shozeb; Li, Wenliang; Lopedota, Angela; Altomare, Cosimo Damiano; Denora, Nunzio; Tuleu, Catherine (MDPI, 2022)
Spironolactone (SPL), a potent anti-aldosterone steroidal drug used to treat several diseases in paediatric patients (e.g., hypertension, primary aldosteronism, Bartter’s syndrome, and congestive heart failure), is not available in child-friendly dosage forms, and spironolactone liquids have been reported to be unpalatable. Aiming to enhance SPL solubility in aqueous solution and overcome palatability, herein, the effects of (2-hydroxypropyl)-β-cyclodextrin (HP-β-CyD) were thoroughly investigated on solubilisation in water and on masking the unpleasant taste of SPL in vivo. Although the complexation of SPL with HP-β-CyD was demonstrated through phase solubility studies, Job’s plot, NMR and computational docking studies, our in vivo tests did not show significant effects on taste aversion. Our findings, on the one hand, suggest that the formation of an inclusion complex of SPL with HP-β-CyD itself is not necessarily a good indicator for an acceptable degree of palatability, whereas, on the other hand, they constitute the basis for investigating other cyclodextrin-based formulations of the poorly water-soluble steroidal drug, including solid dosage forms, such as spray-dried powders and orodispersible tablets.
Keywords: spironolactone; hydroxypropyl-β-cyclodextrin; palatability; cyclodextrin inclusion; phase solubility study; brief-access taste aversion; human taste panel; paediatric formulation